2013
DOI: 10.3329/bjn.v28i2.17172
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Study of Carotid Artery in Patients with Ischemic Stroke

Abstract: Objective: To determine the frequency and characteristics of carotid artery stenosis in acute ischemic stroke patients and to assess the significance of common risk factors for carotid stenosis in these patients. Method: It was cross-sectional observational study which was carried out in neurology department of Bangabandhu Sheikh Mujib Medical University (BSMMU) during the period of January 2010 to December 2011 and one hundred patients admitted with acute ischemic stroke were included in the study. Doppler ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Similar to current study findings report published by Nasreen et al and Sethi et al revealed majority of patients with carotid artery atherosclerosis (56%) of more than 60 years of age with mean age of 60.03 years. 25,26 Gender based distribution of carotid artery atherosclerosis patients reported by Malik et al stated 64% males and 36% females, also the authors reported none of the premenopausal females had lesion and approximately 40% of postmenopausal females had abnormal carotid Doppler which was in close accordance to current study observations. 27 Hemiparesis was observed as the most common clinical presentation in the present study followed by cranial nerve palsies, aphasia and monoparesis, the findings were similar to reports published by Malik et al who reported hemiparesis in majority (76%) of patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to current study findings report published by Nasreen et al and Sethi et al revealed majority of patients with carotid artery atherosclerosis (56%) of more than 60 years of age with mean age of 60.03 years. 25,26 Gender based distribution of carotid artery atherosclerosis patients reported by Malik et al stated 64% males and 36% females, also the authors reported none of the premenopausal females had lesion and approximately 40% of postmenopausal females had abnormal carotid Doppler which was in close accordance to current study observations. 27 Hemiparesis was observed as the most common clinical presentation in the present study followed by cranial nerve palsies, aphasia and monoparesis, the findings were similar to reports published by Malik et al who reported hemiparesis in majority (76%) of patients.…”
Section: Discussionsupporting
confidence: 91%
“…27 Sultana et al reported distribution of degree of stenosis was mild (50%) in 12% of patients, moderate (51-69%) in 50% of patients and severe (>70%) in 20% of patients and near-total occlusion were seen in three (5%) patients also they reported that the presence of stenosis was significantly correlated with older age and the presence of multiple risk factors. 25 Sultana et al reported distribution of degree of stenosis was mild (50%) in 12% of patients, moderate (51-69%) in 50% of patients and severe (>70%) in 20% of patients and near-total occlusion were seen in three (5%) patients also they reported that the presence of stenosis was significantly correlated with older age and the presence of multiple risk factors. 25 These reported findings were in close accordance to current study observations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to degree of carotid artery stenosis: Significant carotid artery stenosis: ≥ 50%, and insignificant carotid artery stenosis: < 50% (8) .…”
Section:  Carotid Duplex Ultrasound (Cdus)mentioning
confidence: 99%